2022
DOI: 10.3390/ijerph191912734
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Disease and Mental Health on Sleep Quality among Migrant Elderly Following Children in Weifang City, China

Abstract: Few studies have focused on the sleep quality among migrant elderly following children (MEFC). This study aimed to investigate the effects of chronic disease and mental health on the sleep quality of MEFC in Weifang, China. A cross-sectional study was conducted by multi-stage cluster random sampling, and in total 613 participants were enrolled. Sleep quality and mental health were assessed by the Pittsburgh Sleep Quality Index (PSQI) and the Depression, Anxiety, and Stress Scale (DASS-21), respectively. Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Furthermore, in previous studies, it was found that the quality of sleep tended to be poorer in subjects with multiple illnesses compared to those with a single disease. [47,48] Our study also identified a considerable proportion of patients diagnosed with comorbidities in addition to cardiovascular disease. Since we did not investigate whether the medication these patients were taking had an impact on their quality of sleep or fatigue, we propose the need for further research as a follow-up study.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, in previous studies, it was found that the quality of sleep tended to be poorer in subjects with multiple illnesses compared to those with a single disease. [47,48] Our study also identified a considerable proportion of patients diagnosed with comorbidities in addition to cardiovascular disease. Since we did not investigate whether the medication these patients were taking had an impact on their quality of sleep or fatigue, we propose the need for further research as a follow-up study.…”
Section: Discussionmentioning
confidence: 80%
“…Bright Lights Urban environments tend to have strong lighting, especially at night. This bright light can disrupt the body's natural rhythm (circadian) and make it difficult for students to fall asleep or maintain quality sleep (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of preserving general health, sleep is just as crucial as diet or exercise (3). Poor sleep quality has been linked to a lower chance of living a longer life (5), along with other risk factors such obesity and weight gain, high blood pressure, high cholesterol, diabetes, atherosclerosis, poor mental health, alcoholism, smoking, bad eating habits, and sedentary behavior (6)(7)(8). Additionally, sleep plays a significant role in brain activities that are critical for work, such as decision-making, attentiveness, and drowsiness (9).…”
Section: Introductionmentioning
confidence: 99%